Implant-Related Complications and Mortality After Use of Short or Long Gamma Nail for Intertrochanteric and Subtrochanteric Fractures: A Prospective Study with Minimum 13-Year Follow-up. Issue 3 (28th September 2017) - Horner, Nolan S.; Samuelsson, Kristian; Solyom, Janos; Bjørgul, Kristian; Ayeni, Olufemi R.; Östman, Bengt
Abstract : Background: The purpose of this study was to evaluate the rates of implant-related complications and mortality after treatment of an intertrochanteric or subtrochanteric fracture with a short or long Gamma nail. Methods: Between September 1998 and August 2003, 644 patients at 2 centers treated with a long or short Gamma nail for a hip fracture were prospectively enrolled in this study. These patients were followed until they reached 1 of the study end points, which included death, a reoperation directly related to the Gamma nail, or the end date of the study. Results: The average age (and standard deviation) of the patients included in the study was 81.3 ± 8.6 years at the time of the operation, and 28.3% of the patients were male. The rate of implant-related complications was 9.9%. The most common complications included peri-implant fracture (4.2%), proximal lateral thigh discomfort requiring extraction of the implant (2.0%), and lag-screw cutout (1.1%). Interestingly, more than half (56%) of the 27 peri-implant fractures occurred >1.5 years after the index operation. The median time from the operation to death was 2.9 years (range, 0 to 17.1 years). The 30-day mortality rate after treatment was 9.5%. Patients with American Society of Anesthesiologists (ASA) class-3 or 4 physical status had a significantly higher risk of mortality than ASA class-1 patients. Conclusions: Gamma nails are effective in the treatment of intertrochanteric and subtrochanteric fractures. However, 9.8% of patients had complications requiring additional surgery. The most common serious complications include peri-implant fracture and lag-screw cutout. Several peri-implant fractures occurred long after the index procedure. Patients had a high rate of mortality (27%) after 1 year, and higher preoperative ASA class was found to be a predictor of increased risk of mortality. Therefore, clinicians must carefully consider patients' preoperative comorbidities when counselling patients on the risks of surgery. Level of Evidence: TherapeuticLevel II . See Instructions for Authors for a complete description of levels of evidence.